2019
DOI: 10.3389/fphys.2019.01252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plantar Mechanical Stimulation on Anabolic and Catabolic Signaling in Rat Postural Muscle Under Short-Term Simulated Gravitational Unloading

Abstract: It is known that plantar mechanical stimulation (PMS) is able to attenuate unloading-induced skeletal muscle atrophy and impaired muscle function. However, molecular mechanisms underlying the effect of PMS on skeletal muscle during unloading remain undefined. The aim of the study was to evaluate the effects of PMS on anabolic and catabolic signaling pathways in rat soleus at the early stages of mechanical unloading. Wistar rats were randomly assigned to ambulatory control, hindlimb suspension (HS) for 1 or 3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 93 publications
4
28
1
Order By: Relevance
“…At the same time, literature analysis indicates that the molecular mechanisms underlying the maintenance of the structural and contractile characteristics of postural muscles during the PMS under unloading conditions have not been thoroughly studied. In our laboratory, it was previously shown that PMS can prevent a decrease in the rate of global protein synthesis and changes in 4E-BP1, GSK-3β, AMPK phosphorylation in rat soleus muscle under short-term hindlimb suspension 31 . It was also demonstrated that the application of PMS during short-term unloading (1–3 days) can prevent or attenuate an increase in MuRF-1 mRNA expression 31 , a decrease in MyHC Iβ expression via calcineurin-NFATc1 signaling pathway 32 as well as the loss of neuronal NO-synthase 33 .…”
Section: Introductionmentioning
confidence: 97%
“…At the same time, literature analysis indicates that the molecular mechanisms underlying the maintenance of the structural and contractile characteristics of postural muscles during the PMS under unloading conditions have not been thoroughly studied. In our laboratory, it was previously shown that PMS can prevent a decrease in the rate of global protein synthesis and changes in 4E-BP1, GSK-3β, AMPK phosphorylation in rat soleus muscle under short-term hindlimb suspension 31 . It was also demonstrated that the application of PMS during short-term unloading (1–3 days) can prevent or attenuate an increase in MuRF-1 mRNA expression 31 , a decrease in MyHC Iβ expression via calcineurin-NFATc1 signaling pathway 32 as well as the loss of neuronal NO-synthase 33 .…”
Section: Introductionmentioning
confidence: 97%
“…At the same time, Suzuki and colleagues minced the soleus muscle tissue and measured NO content at room temperature [ 31 ] so these differences in the experimental procedures could lead to discordant results. A number of evidences concerning the states of NO-dependent signaling pathways, such as Akt-independent GSK-3beta activation during the early stage of hindlimb unloading [ 26 , 44 ], indirectly support the suggestion that NO content in soleus muscle tissue is more likely to decrease than increase under unloading conditions. However, neuronal NOS does not significantly contribute to prevention of atrophy during soleus muscle stretching upon rat hindlimb suspension, but is involved in the maintenance of expression of some muscle proteins, in particular in the regulation of MHC I mRNA expression upon muscle stretching [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recently Chibalin et al, 2018 showed an increase in PKA activity in rat soleus muscle after 6 and 12 h of HS [ 34 ], so it is unlikely that this protein kinase is responsible for a decrease in inhibitory GSK3β Ser9 phosphorylation at this stage. In addition, a decrease in AKT Ser473 phosphorylation in rat soleus after 24 h of unloading was not prevented by foot mechanostimulation, while a decrease in GSK3β Ser9 phosphorylation was successfully prevented by mechanostimulation [ 14 ]. It was found that GSK3β can be phosphorylated on Ser9 by one of the cGMP-dependent protein kinases (most likely by protein kinase G) [ 115 , 116 ].…”
Section: Nitric Oxide: Friend or Foe In Signaling Remodeling? Locamentioning
confidence: 99%
“…GSK3β is also able to reduce the intensity of rRNA synthesis through ubiquitylation of proto-oncogene c-Myc, a key regulator of the expression of ribosomal genes [ 120 ]. We first found a significant decrease in the rate of protein synthesis and 18S and 28S rRNA content in rat soleus muscle after 24 h of HS, accompanied by a decrease in the content of GSK3β Ser9 phosphorylation indicating an increase in the GSK3β enzymatic activity [ 14 ]. GSK3β can also have a negative impact on mitochondrial dynamics.…”
Section: Nitric Oxide: Friend or Foe In Signaling Remodeling? Locamentioning
confidence: 99%
See 1 more Smart Citation